Is Clipping Superior to Cauterization in the Treatment of Palmar Hyperhidrosis? - Findikcioglu, Alper; Kilic, Dalokay; Hatipoglu, Ahmet (The Thoracic and Cardiovascular Surgeon, 2014)
Background Endoscopic thoracic sympathectomy has been accepted as the most effective treatment for palmar hyperhidrosis (PH). However, there is a debate regarding the surgical techniques in terms of effectiveness, recurrence, and reversibility. In this study, sympathetic chain disruptions were compared in terms of whether the clipping or ablation technique had an effect on the long-term outcomes of patients who underwent thoracic sympathectomy for primary PH.Patients and Methods All patients who underwent video-thoracoscopic sympathectomy for PH between May 2008 and October 2011 were included. Single-port bilateral sympathectomy was performed depending on the sweat distribution. As a standard approach, rib-based terminology was used to describe the blockade level of the sympathetic ganglia, and single-level R3 sympathectomy (between R3 and R4) was performed in all patients. The type of sympathectomy was changed. Monopolar electrocautery was first performed and 5-mm clips were then used for nerve disruption. Both techniques were evaluated and compared in terms of effectiveness, reversibility, and recurrence.Results Cauterization of the sympathetic chain was applied in 28 (47%) (Group A) patients and clipping in 32 (53%) patients (Group B). CH was the most common adverse effect and was observed in 43 (71.6%) patients (Group A, 71.4%; Group B, 71.8%; p = 0.8). The success rate was 93% for Group A and 100% for Group B (p = 0.15). The satisfaction rate for Group A was 83% and for Group B was 86% (p = 0.77). In Group A two patients (7%), and in Group B three patients (9%) requested reversibility because of severe compensatory hyperhidrosis. Overly dry hands were the other most common side effect and were identified in 12 (25%) patients. Recurrences were observed in 11 patients in Group A and 4 patients in Group B (19 vs. 6%; p = 0.01). The mean follow-up time was 33 ± 10.5 months (range, 13–53 months).Conclusion Both clipping and cauterization are highly effective for the treatment of PH. The methods are comparable in terms of effectiveness and side effects despite the fact that the recurrence rate was higher in the cauterization group. Potential reversibility of compensatory sweating was not observed in our series. Identification of ideal candidates for surgery and education of patients about the permanent side effects of sympathectomy might make these techniques more convenient.
Keywords: thoracoscopy/VATS; quality of life; hyperhidrosis